DJing & Reading the Crowd in an EDM Context from a Second Person Perspective - Marchiano, María (2021)
Background: DJing is a performance where a DJ plays pre-made electronic dance music’s tracks (EDM) for a dancing crowd during a party. DJs claim they read the crowd in order to play music (Broughton & Brewster, 2002), making DJ-audience interaction very relevant to DJing. The active participation of the crowd that the party requires makes a difference from other performer-audience situations. We think that this could be a case of Second Person Interaction, whose main features involve face-to-face exchanges, direct perception of mental states in others’ body expressions, psychological attributions, changes in both mental states and reciprocal actions (Pérez & Gomila, 2021). Both the musical performance and the one-to-many interaction’s features involved in DJing has not yet been fully described from a second-person perspective. Aims: The research aimed to describe DJ-crowd interaction from the DJ’s perspective, identify its second person features, and analyze the impact of this interaction on music.